Exercise and Syzygium aromaticum reverse memory deficits, apoptosis and mitochondrial dysfunction of the hippocampus in Alzheimer's disease. (25th March 2022) - Panahzadeh, Fatemeh; Mirnasuri, Rahim; Rahmati, Masoud
Abstract: Ethnopharmacological relevance: Alzheimer's disease (AD), the most common disease in the brain, is associated with cognitive and mitochondrial dysfunction. Emerging evidence suggests that endurance training and Syzygium aromaticum (L.) Merrill and Perry (Myrtaceae) (commonly referred to as clove ) are effective interventions to maintain oxidative balance and improve cognitive function. Aim of the study: The present study aimed to investigate the effect of endurance training and clove oil affect spatial memory, apoptosis, mitochondrial homeostasis, and cognitive function in Alzheimer's rats. Materials and methods: 81 rats were randomly assigned to 9 groups: Healthy (H), sham (sh), Healthy-exercise (HE), Healthy-clove (HC), Healthy-exercise-clove (HEC), Alzheimer's (A), Alzheimer's-exercise (AE), Alzheimer's-clove (AC), and Alzheimer's-exercise-clove (AEC). Alzheimer's induction was induced by the injection of 1–42 amyloid into the CA1 region of the hippocampus. The exercise training protocol was performed for 3 weeks, every day for 30 min in swimming training, and clove oil supplementation (0.1 mg/kg) was gavaged daily for 3 weeks in the supplement rat. Shuttle box test was used to measure spatial memory after the last training session, and to determine the mRNAs and protein levels and apoptosis, Real-Time PCR, immunofluorescent, and tunnel methods were used, respectively. Results: Alzheimer's caused a significant decrease in the PRDX6 and GCN5L1 mRNAs and protein levels and a significant increase in apoptosis in the hippocampus of the Alzheimer's group compared to the control group (P = 0.001). Alzheimer's also reduced the time delay in entering the dark environment and increased the time spent in the dark environment (P = 0.001). Following endurance training and consumption of clove oil, spatial memory (P = 0.001), apoptosis (P = 0.001) and mRNAs and protein levels of PRDX6 (P = 0.001) and GCN5L1 (P = 0.017), were recovered in AE, AC and AEC groups, as compared with A group. Conclusion: Swimming training and consumption of clove can possibly be considered as an effective intervention to maintain oxidative balance and improve mitochondrial homeostasis in Alzheimer's disease. Graphical abstract: Image 1